A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae) - Qiu, Lu; Che, Yang-Li; Wang, Zong-Qing (Zootaxa, 2018)
The cockroach genus Eupolyphaga is revised. Twenty species and two subspecies are recognized, with thirteen species and two subspecies are new to science: E. daweishana sp. nov., E. dongi sp. nov., E. fengi sp. nov., E. hanae sp. nov., E. hupingensis sp. nov., E. maculata sp. nov., E. nigrifera sp. nov., E. nigrinotum sp. nov., E. pilosa sp. nov., E. robusta sp. nov., E. shennongensis sp. nov., E. wooi sp. nov., E. xuorum sp. nov., E. everestiana reni subsp. nov., and E. fengi yongshengensis subsp. nov. Homœogamia sinensis Saussure is placed as a junior synonym of E. sinensis (Walker) and the replaced name E. limbata (Kirby) for Homœogamia sinensis is invalid, the status of Eupolyphaga thibetana (Chopard) is recovered. Male genitalia of species in the genus is described and illustrated. Females and oothecae of some species are described and illustrated. Distribution maps and a checklist of Eupolyphaga are provided. A key to males of Eupolyphaga is given. Plenty habitat photographs are shown.